Life-threatening course of pemphigus vulgaris complicated by sepsis caused by azathioprine-induced bone marrow suppression, successfully managed with combination therapy - Tichy, Martin; Urbanek, Jaroslav; Sternbersky, Jan; Ditrichova, Dagmar; Hercogova, Jana (Dermatologic therapy, 2014)
Severe forms of pemphigus vulgaris (PV) that are resistant to standard treatment present a life-threatening disease with a mortality of 5-10%. The treatment is usually individualized. The most popular procedures used today include intravenous applications of immunoglobulins and rituximab. Currently the common use of pulse corticosteroids, often in first-line treatment, is being neglected. This particular case documented the severity of the disease and also the need for combined and comprehensive care, in which corticosteroid pulse therapy still plays an important role.
Keywords: Azathioprine; pulzní dávkování léků; Immunosuppressive Agents; own experience; Sepsis; Pemphigus; Anti-Bacterial Agents; azathioprin; Time Factors; výsledek terapie; intravenózní imunoglobuliny; Drug Therapy, Combination; Middle Aged; Biopsy; Antifungal Agents; Immunoglobulins, Intravenous; recidiva; therapeutic possibilities; pemfigus; kombinovaná farmakoterapie; ženské pohlaví; leukopenie; imunosupresiva; Humans; Recurrence; Skin; časové faktory; antibakteriální látky; sepse; lidé středního věku; resistant form of pemphigus vulgaris; biopsie; Leukopenia; hormony kůry nadledvin; Pulse Therapy, Drug; Female; Treatment Outcome; kůže; Adrenal Cortex Hormones; lidé; antifungální látky